Dispute over Sasak Customary Inheritance Rights and the Evolution of Granting Inheritance Rights to Girls - Makhrup, Abdul Gani (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
A central concern in disputes concerning customary inheritance rights within the Sasak community of West Nusa Tenggara, Indonesia, pertains to the allocation of inheritance rights to daughters. This article examines recent modifications to the Sasak custom of granting inheritance rights to females, in addition to the historical and cultural context surrounding these rights. In accordance with empirical normative research, the author demonstrates that traditional inheritance practices are shifting to grant daughters inheritance rights. Multiple factors, including modernization, the legalization of gender issues, and social demands, support this. The complexities of granting females inheritance rights in traditional Sasak society and the resulting social and cultural transformations in the region are examined in this study. In Sasak customary law, the following elements contribute to disputes over the inheritance of girls: 1). Religious factors impede the development of customary law and legal choice (